Construction of solitary wave solutions of bi-harmonic coupled Schrodinger system through f6-methodology - Iqbal, Muhammad Sajid; Hashemi, M. S.; Naeem, Rishi; Tarar, Muhammad Akhtar; Farheen, Misbah; İnç, Mustafa (Springer, 2023)
The existence of solutions of coupled system of bi-harmonic Schrodinger equations as fixed point of an operator has been given in this article. The corresponding estimates for the length of continuity of solutions have been constructed. By applying new phi(6) model expansion, exact traveling wave solutions of the system have been extracted in the form of Jacobi elliptic functions. Particularly, trigonometric and hyperbolic functions can be obtained by applying the limits to Jacobi elliptic functions tending to zero or 1. The obtained solutions have been simulated and the resulting smooth waves have been plotted.
Keywords: Nonlinear partial differential equations; Exact solutions; phi(6) method